First report of Erwinia pyrifoliae causing flower blight and fruit rot on greenhouse-grown Fragaria × ananassa in the United States - Bonkowski, John; Yasuhara-Bell, Jarred; Creswell, Tom (Plant disease, 2024)
Erwinia pyrifoliae causes disease of pear (Pyrus spp.), apple (Malus spp.), and strawberry (Fragaria × ananassa) (Wenneker and Bergsma-Vlami 2015), which are economically important commodities in the US. Disease symptoms on pear and apple are indistinguishable from those caused by the non-quarantine fire blight pathogen, E. amylovora (Kim et al. 1999), which also causes disease on strawberries (Atanasova et al. 2005). Samples of greenhouse-grown strawberry 'Albion' from Ohio were submitted to the Purdue Plant and Pest Diagnostic Lab in December 2023. Fruits were stunted with brown lesions, while sepals and pedicels had brown-black water-soaked lesions. Cut fruit exuded bacterial ooze from the main vascular bundle. Bacterial streaming was observed microscopically from symptomatic tissue which tested positive with the E. amylovora ImmunoStrip® (Agdia Inc., Elkhart, IN); reported by the manufacturer to cross-react with E. pyrifoliae. Isolation from symptomatic tissue produced pure cultures on sucrose peptone agar and Kings medium B after incubation at 27°C for 48 hr, and colonies appeared circular and white/opaque. Crude DNA extractions were prepared by boiling colony suspensions in Tris-EDTA buffer. Two independent real-time PCR tests specific for E. pyrifoliae (Lehman et al. 2008; Yasuhara-Bell et al. 2024) produced positive results. Conventional PCR using an E. pyrifoliae-specific primer set targeting a divergent region between pstS and glmS genes (Wensing et al. 2011) also produced positive results. The amplicon was Sanger-sequenced and deposited into NCBI GenBank (Accession PP757383). BLASTn analysis using the Nucleotide collection and Whole-genome shotgun contigs revealed top matches (100% query coverage; 97.5% identity to type strain DSM 12163) with E. pyrifoliae only; next closest match was E. amylovora (53% query coverage). To confirm Koch's postulates, immature fruit of six healthy strawberry 'Albion' plants were wounded with a sterile pipette tip and then submersed in a bacterial suspension in sterile deionized water (DI H2O) (3.1×107 cells/ml). Fruit of six additional plants were mock inoculated using sterile DI H2O. Plants were placed in plastic bags for 48 hr at room temperature with a 12-hr photoperiod. Symptoms were first observed on inoculated plants 1.5 days post-inoculation (DPI). Brown discoloration was observed within fruit and as spreading lesions on fruit pedicels by 4 DPI; mock-inoculated plants remained asymptomatic. Bacterial streaming from symptomatic tissue allowed successful re-isolation of the bacterium. Molecular testing confirmed isolates to be E. pyrifoliae, thus completing Koch's postulates. Following initial confirmation, additional samples of infected strawberry ('Albion' and 'GB96') from the same greenhouse were confirmed positive for E. pyrifoliae by molecular testing and sequencing. To our knowledge this is the first time Erwinia pyrifoliae was detected in the US. There are many known pathways of introduction from Asia and Europe; however, pstS-glmS sequence comparison with strawberry isolates from the Netherlands (sequences provided by M.J.C. Pel) suggests this US strawberry strain is unique, but most closely related to Japanese strains (98.5% identity). Potential origin of this strain is unknown, but comparative genomics studies to investigate relatedness among strains are planned.